2015
DOI: 10.1097/crd.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Novel Perspectives on Arrhythmia-Induced Cardiomyopathy

Abstract: Arrhythmia-induced cardiomyopathy is a partially or completely reversible form of myocardial dysfunction due to sustained supraventricular and ventricular arrhythmias. Asynchrony, rapid cardiac rates and rhythm irregularities are the main factors involved in the development of the disease. The reversible nature of arrhythmia-induced cardiac dysfunction allows only for a retrospective diagnosis of the disease once cardiac function is restored following heart rate control. A high level of suspicion is needed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The potential triggering arrhythmias considered were: Atrial fibrillation (AF), atrial flutter, supraventricular tachycardia, ventricular tachycardia and premature atrial and ventricular complexes. More specifically, this study considered significant > 20000 premature ventricular complexes per day, according to the current available literature [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential triggering arrhythmias considered were: Atrial fibrillation (AF), atrial flutter, supraventricular tachycardia, ventricular tachycardia and premature atrial and ventricular complexes. More specifically, this study considered significant > 20000 premature ventricular complexes per day, according to the current available literature [8].…”
Section: Methodsmentioning
confidence: 99%
“…To this day, two categories of the disease have been described: Arrhythmia-induced TCM, where the arrhythmia is the sole reason for the dysfunction, and arrhythmia-mediated TCM, where the arrhythmia can exacerbate or worsen heart failure (HF) or an underlying heart disease [1]. The former can also be referred to as “pure” TCM and the latter as “impure” TCM [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Two large retrospective studies demonstrated that apixaban, dabigatran and rivaroxaban are associated with a lower risk of AKI compared to warfarin (Figure 4) [26,65]. Overall, VKA administration is still considered a major risk factor for AKI, as a result of vascular calcification due to inhibition of the vitamin-Kdependent matrix gamma-carboxyglutamate protein (MGP), as depicted in Figure 5 [66][67][68][69][70]. Similar findings were also reported in a cohort of AF patients undergoing percutaneous coronary intervention; after administration of contrast medium, patients taking DOACs, especially dabigatran, showed a better control of renal function than patients on warfarin with a trend toward a reduction in the incidence of AKI [71].…”
Section: Anticoagulant-related Nephropathy and Progression Of Kidney mentioning
confidence: 99%
“…In the setting of acute heart failure and frequent VAs may be challenging to determine if VAs are causes or consequences of heart failure. Arrhythmia‐induced cardiomyopathy is a partially or totally reversible disease in which left ventricular dysfunction is induced or mediated by atrial or ventricular arrhythmias . The detection of this condition requires a high level of suspicion for the presence of persistent arrhythmia with otherwise unexplained cardiomyopathy, and the diagnosis may be evident only after restoration or maintenance of sinus rhythm or after aggressive rate control.…”
Section: Discussionmentioning
confidence: 99%